PENGARUH PEMBIAYAAN KREDIT USAHA RAKYAT TERHADAP PENDAPATAN USAHA MIKRO KECIL DAN MENENGAH DI PT. PEGADAIAN SYARI’AH UNIT KARANG BARU - Khilda Amalia (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to find out how the People's Business Credit (KUR) financing process is carried out by PT. Pegadaian Sharia Unit Karang Baru and how much influence People's Business Credit (KUR) financing has on the income of Micro, Small and Medium Enterprises (MSMEs) partially. The type of research used is field research with a quantitative approach. The population used in this research were 229 customers of the PT. Sharia Pegadaian Karang Baru Unit. The sample was selected using the incidental sampling method and calculated using the Slovin formula as many as 70 respondents. The data used in this research is primary data obtained from respondents who filled out the questionnaire. The results of this research show that people's business credit financing obtained a t count value of 15.175 and a t table of 1.66757 with a significant value of 0.000 at a significance level of 0.05. Based on these results it can be seen that t count > t table where 15.175 > 1.66757 and a significant value where 0.000 < 0.05 which means that Ho is rejected and Ha is accepted, so it can be said that the KUR financing variable (X) partially has a positive and significant effect on the income of MSME (Y) customers of PT. Pegadaian Sharia Unit Karang Baru